Ammonolysis of Ga2O3 and its application to the sublimation source for the growth of GaN film - Park, YJ; Oh, CS; Yeom, TH; Yu, YM (ELSEVIER SCIENCE BV, 2004)
We investigated the ammonolysis of Ga2O3 for the application of source material to the sublimation method. The abrupt change of local structure was observed at the temperature above 1050degreesC while it began to appear at 950degreesC. It was confirmed from the study of ammonolysis of beta-Ga2O3 single crystals that the oxygen atom of octahedron site was preferably substituted by the nitrogen atom rather than that of tetrahedron site. The crystallographically different tetrahedron and octahedron oxygen sites were elucidated by electron paramagnetic resonance (EPR) study on Cr3+ ions in Ga2O3 single crystal doped with Cr. The GaN film was grown by the sublimation method using Ga2O3 as a source material, although the thickness of GaN was relatively thin compared to GaN source material. The ammonolysis of Ga2O3 can provide an alternative useful technology for the preparation of GaN film. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: NANOCRYSTALLINE GALLIUM NITRIDE; ELECTRON-PARAMAGNETIC-RESONANCE; BETA-GA2O3; CRYSTALS; AMMONIA; ROUTE; MELT